A review on non-economic legacies of business events - Tan, Ai Ling; Sivakumari, Supramaniam *; Vijaya, Malar V Arumugam *; Ng, Siew Cheng * (2024)
The global expansion of business events has led to an increase in organizations hosting events, attracting participants from around the world, and promoting the host countries as travel destinations. While past research has primarily focused on the economic impact of these events, this paper seeks to address the gap in understanding the non-economic legacies of business events. Through a review of related literature from 2010 to 2020, the paper examines a sample of 37 articles and identifies emerging themes related to social, cultural, and environmental legacies that extend beyond the management period of the business event. The paper contributes an initial conceptual framework that highlights the impact of non-economic legacies on social, economic, and environmental factors, and proposes future research avenues for different stakeholders.